Forms of sulfur in Brazilian Oxisols under no-tillage system - Blum, Susana Churka (2012)
Soil is a critical component of the global sulfur (S) cycle acting as source and a sink for various S species and mediating changes of S oxidation states. However, very little is known about the identities of these specific organic and inorganic S containing molecules, especially in Brazilian soils under no-tillage (NT) system. Thus, the objectives of this study were: (i) to report long and medium term effects of the application of lime and up to 12 t ha-1 of phosphogypsum (PG) in samples from two Oxisols collected in field experiments carried out under no-tillage (NT) systems; (ii) to assess the effect of PG application on the amount, form and distribution of organic and inorganic S pools in soils under NT comparing to a natural forest ; (iii) to investigate C, N and S mineralization/immobilization in soil samples affected by plant residues and biochar, thus identifying the major transformations in the S fractions. After 13 years of lime application in a loamy Oxisol, changes in soil acidity and exchangeable Ca2+ ad Mg2+ supply were visible up to 80 cm depth. The effect of PG providing Ca2+ and S-SO4 2- were more pronounced at lower depths. S-SO4 2- distribution in the soil profile was mostly correlated with contents of free dithionite extractable Fe (Fed) and amorphous dithionite extractable Fe minus oxalate extractable Fe (Fed-Feo). There was no effect of lime and PG in maize grain yield, showing that the plants were unable to benefit of the soil ameliorations. An appreciable movement of sulfate to the subsoil was observed in soil samples from a clayey Oxisol, even in a medium-term (after 3.5 years), despite the fact that the soil had presented high SO4 2- adsorption capacity. In this area, PG had positive benefits in cereal crop yield due to the supply of Ca2+ and S-SO4 2-. PG application and changes in landuse practice alters both quantitative (evaluated by the wet-chemical technique) and qualitative (evaluated by means of X-Ray Near Edge Structure - XANES spectroscopy) composition of S functional groups in this wet subtropical Brazilian soil under NT. Compared to the forest site, soils under NT system had lower amounts of organic C, total N and total S Sulfur losses due to cultivation were higher than losses of C and N, and the use of fertilizers containing S seems to be vital for the recovery of S moieties. The dynamics of the plant materials decomposition was mostly governed by the C/S ratio. Sulfur mineralization was driven by the form of S in the starting materials rather than S concentration in the tissue, as revealed by XANES. The incorporation of plant residues and biochar led to an increase in the amount of ester sulfate in the early stage of incubation, which was further mineralized and had a steady decline at the end of evaluation. These findings encourage further investigations of biochar as S source, involving particularly chars produced from different feedstocks and pyrolysis temperatures.